Phospholipase A2 enhances the endothelial cell detachment effect of a snake venom metalloproteinase in the absence of catalysis - Bustillo, Soledad (2015)
Microvessel disruption leading to hemorrhage stands among the most dangerous consequences of envenomings by snakes of the family Viperidae. A PIII metalloproteinase (SVMP), balteragin, purified from the venom of the snake Bothrops alternatus, displays a potent hemorrhagic effect, and a moderate myotoxicity in vivo. Previous studies described the ability of this SVMP to induce the detachment of C2C12 myoblasts in culture, without causing cytolysis. Surprisingly, a purified acidic phospholipase A2 (PLA2) from the same venom was found to increase this detaching activity of the SVMP on myoblasts. Since endothelial cells are a natural target of SVMPs in vivo, the possibility that this synergistic effect is also observed on this cell type was explored in the present work. In addition, a first approach of the mechanism of action of this effect was studied. Results clearly confirm that the acidic PLA2, despite lacking toxicity towards endothelial cells, significantly enhances the detaching effect of the SVMP even at a concentration as low as 1 μg/mL. Inhibition of enzymatic activity of the PLA2 by chemical modification with p-bromophenacyl bromide did not affect the synergistic activity, suggesting that this effect is not dependent on phospholipase enzymatic activity and may instead be the consequence of an interaction of the PLA2 with endothelial cell plasma membrane. To our knowledge, this is the first report of a synergistic action of a non toxic PLA2 in enhancing the detachment of endothelial cells induced by a metalloproteinase.